Analisis Layanan Kesehatan IGD RSUD Kota Tanjungpinang Menggunakan Lean Six Sigma - Amirrudin, Amirrudin; Priyatno, Agus; Sugilar, Sugilar (Jurnal Pendidikan Indonesia, 2025)
Public services in the health sector, such as in the Emergency Room of Tanjungpinang City Hospital, face challenges due to the increasing number of patient visits influenced by the JKN policy, limited staff, and inadequate facilities, resulting in long waiting times for patients to be transferred to inpatient rooms. This condition has a negative impact on patients and often raises public complaints. To overcome this problem, analysis is needed to find solutions such as the implementation of the lean Six Sigma method which aims to increase efficiency by reducing non-value-added activities, as well as adjusting hospital service standards to be higher than national standards. With this innovation, it is hoped that services will be faster, of higher quality, and able to meet public demands. This research is qualitative analytical with observational action process research method which is a reference for Lean Thinking and Six Sigma with DMAIC (Define, Measure, Analyze, Improve and Control) Tools. Problem analysis obtained a picture of the health service process in the Emergency Room of Tanjungpinang City Hospital experiencing a waiting time or non-value added activities of around 201 minutes (57.59%) from a total average time of 349 minutes, or a total value added activity of only 148 minutes (42.41%). from the results of direct observation of around 333 patients who visited the Emergency Room of Tanjungpinang City Hospital during 14 days of observation, it was still found that around 13% of visits exceeded the maximum time for patient transfer from the Emergency Room to the inpatient room or were at the sigma level, namely level 2.6. From this study, it can be assumed that the lean Six Sigma method is not only suitable for use in the private sector but has also proven to be effective in the public sector, even in the health sector.